DETERMINATION THE MOST IMPORTANT OF HSE CLIMATE ASSESSMENT INDICATORS CASE STUDY: HSE CLIMATE ASSESSMENT OF COMBINED CYCLE POWER PLANT STAFFS - Reza; Maryam; Saghar; Vahid (Journal CleanWAS, 2017)
Doubtlessly, noting the growth of industry and the criticality of the environment at the present time and the significance of protecting and preserving the resources to achieve the sustainable development, establishing the appropriate cultural mechanisms which can be able to confront the probable problems rationally besides understanding the biological and human resources for achieving the goals of sustainable development and establish matching with the conditions is so necessary. Today, the subject of HSE in the industry and creating its relevant cultural context in the developing countries is significant and it is necessary to assess its position at the organizational level in several sessions. Assessing the climate of HSE in an organization can depict a realistic picture of the staff understanding of the subject of HSE and their duties. The purpose of carrying out this study is to identify the main assessing factors of the climate of HSE in an organization and studying one of the industrial units in order to determine the position of them with a view to HSE. This descriptive-analytical study is being carried out based on the review of the literature and its results to identify the factors of HSE climate and then assessing the climate of HSE among the staff of a combined cycle power plant. The survey (questionnaire) contains forty-three questions and is adjusted based on the 9- point Likert Scale Eight factors are being determined by means of an appropriate correlation for assessing the HSE climate. The validity of the questionnaire was achieved by means of Cronbach’s Alpha coefficient of 0.727 and the final result of the questionnaire evaluates an intermediate climate of HSE in the organization.